The Concept Of Islamic Identity And Its Importance For Muslim Youth - Gaya, Shahbaz; Ahmad, Nadzrah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objective: This study seeks to identify the key components of an Islamic identity as derived from the Qur’an, aimed at fostering the development and preservation of Muslim youth. Research Method: The study utilized an inductive approach, analyzing the Qur’an to extract components of Islamic identity pertinent to youth development. Results: The findings reveal that Islamic identity is defined by its core belief system, a unified connection to a global ummah, and a profound influence on both the private and public lives of Muslims. Findings and Implications: The identified components specifically address significant threats that Muslim youth encounter in their efforts to preserve their Islamic identity, including peer pressure, assimilation, materialism, corrupt desires, religious doubt, societal disconnection from religion, and Islamophobia. These components serve as vital anchors for establishing and maintaining the faith of young Muslims. Conclusion: Understanding and developing an Islamic identity is essential for Muslim youth to uphold their faith, particularly during challenging times. Contribution: This research enhances our understanding of how an Islamic identity, rooted in Qur’anic teachings, can assist Muslim youth in navigating contemporary challenges to their faith and identity within diverse social contexts. Limitations and Suggestions: While the abstract highlights potential ramifications of failing to preserve Islamic identity, such as loss of trust and engagement in oppression and sin, it does not explicitly address the research limitations or offer specific suggestions for further inquiry in this area.